Examining the Association of Grit Profiles With Big Five Personality and Achievement Among Iranian Foreign Language Learners - Khodaverdian Dehkordi, Maryam; Jabbari, Ali Akbar; Mazdayasna, Golnar (Frontiers in Psychology, 2021)
Grit— trait-level perseverance and prolonged passion for primary goals— is related to several indicators of educational success such as academic achievement, engagement, and motivation. Although there is new evidence showing the beneficial effects of grit, most research has taken a variable-focused approach and consequently has failed to indicate how individuals with different grit profiles might have different academic results. The present study aimed to build on the existing literature on grit by investigating the relationship between grit, big five personality and L2 achievement. The participants of this study were 384 English as a Foreign Language (EFL) students from different academic majors studying at Yazd University. They had enrolled in General English (GE) courses. The results of the cluster analyses showed that there were three natural grit profiles (Cluster 1 = High Perseverance and High Consistency; Cluster 2 = High Perseverance and Low Consistency; Cluster = Low Perseverance and High Consistency) in the current study. The results of the multivariate analysis of variance (ANOVA) showed that students belonging to cluster 1 had the highest scores on big five personality traits and L2 achievement. The results also showed that when taking academic exams, high perseverance of effort and low consistency of interest were related to higher level of neuroticism and lower level of consciousness.